Foreign economic activity management features - Kirdasinova К.А; Turmakhanbetova, Sh.Sh.; Mihayi, P. (BUKETOV BUSINESS REVIEW, 2017)
In connection with the ongoing integration management processes of national economy of Kazakhstan, at this moment it is quite urgent to study issues in the field of international economic relations. Foreign economic activity in Kazakhstan is implemented both on the state level and at the level of individual economic entities. Rational foreign economic policy of the state can lead to the increasing in the rate of growth of the national income, to the acceleration of scientific and technological progress, to increase concentration of production and efficiency of capital investments. It is studied by the authors of the article the conceptual apparatus of foreign economic activity. Economic analysis of the dynamics of foreign trade turnover of the Republic of Kazakhstan is carried out. The conceptual approaches of import-economic operations are studied. Considered export-import operations for some groups of food products, the main sales markets for products. The structure of export and import of goods of Kazakhstan according to the degree of their processing is presented. Also presented in the dynamics of data on exports, imports of goods. Basically, the import of the Republic of Kazakhstan is represented by intermediate goods (raw materials for processing) and means of production. About the increase in the average annual rate of renewal of the country’s industrial and technological park. According to the results of study. Mainly, the Republic of Kazakhstan is formed infrastructure of foreign economic activity management. There is an international representation about the republic as a serious and reliable partner. The necessary prerequisites about integrating Kazakhstan into world economic relations are laid.